2017
DOI: 10.3233/ch-168039
|View full text |Cite
|
Sign up to set email alerts
|

Differences of standard values of Supersonic shear imaging and ARFI technique – in vivo study of testicular tissue

Abstract: SSI values are significantly higher than ARFI values when measuring the stiffness of testicular tissue and should only be compared with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In addition to intra-testicular shear wave velocity variability, a previous study demonstrated significant differences in shear wave velocities measured on different machines [12]. Trottmann et al [13] showed that values obtained using SuperSonic Imaging were significantly higher than those measured using VTIQ in 58 healthy testes which suggests that shear wave velocity values are not interchangeable across different commercial systems; a similar limitation has been found for the shear wave assessment of liver fibrosis.…”
Section: Normal Testesmentioning
confidence: 94%
“…In addition to intra-testicular shear wave velocity variability, a previous study demonstrated significant differences in shear wave velocities measured on different machines [12]. Trottmann et al [13] showed that values obtained using SuperSonic Imaging were significantly higher than those measured using VTIQ in 58 healthy testes which suggests that shear wave velocity values are not interchangeable across different commercial systems; a similar limitation has been found for the shear wave assessment of liver fibrosis.…”
Section: Normal Testesmentioning
confidence: 94%
“…For testicular lesions, the values obtained for SWE vary between different machines and are not interchangeable [391]. The prob-lems associated with the areas of fibrosis adjacent to the tunica albuginea hamper the assessment of focal lesions adjacent to this region [392].…”
Section: Limitations and Artifactsmentioning
confidence: 99%
“…Thickening of the tendon, loss of echo texture, and gaps can be recognized by comparing with healthy individuals [13]. In elastography, a healthy tendon will appear firm, while the ruptured one and the one with tendinopathy will be softer [14][15][16]. With this background, our goal was to measure the softness and thickness of the Achilles tendon in patients and assess its association with hypercholesterolemia.…”
Section: Introductionmentioning
confidence: 99%